Avicenna (IbnSina) aspect of Ileus - Mostafa Salehi Nagafabadi; Seyde Sedighe Yousefi; Asie Jokar; Mohamad Askarfarashah (International Journal of Life Sciences, 2015)
Dear Editor, Ileusis derived from the Greek word 'eileos,' which means twisting, a prevalent and non- prophylactic consequence in major abdominal operations (Jonson &Walsh 2009) that although it is not life threatening, may expose the patients to morbidity (Nimarta&Neena& Gupta 2013). Ileus is a lack of intestinal peristalsis without mechanical obstruction (Jonson &Walsh 2009); it occurs post-operatively, ileus (PI) is a delay in the return of a normal bowel movement, which typically lasts 3-5 days dependent on the location, 0 to 24 hours in the small intestine, 24 to 48 hours in the stomach, and 48 to 72 hours in the colon respectively (Ianey2004)(Rychter&Clavé 2013) The patients diagnosed with this postoperative state, Ileus, are problematic issues that may occur due to an inflammation, deranged neural input, or medications taken in conjunction with the surgery. The patient susceptibility to this postoperative state may occur following a major intra-or extra-abdominal surgery, or manipulations of the intestines during various other a surgeries(Jonson &Walsh 2009). The pathogenesisof Postoperative Ileus (PI) is unknown(Rychter&Clavé 2013). To date, no clear-cut therapy is known for postoperative ileus )(Rychter&Clavé 2013), but several methods are administered to reduce incidence of postoperative ileus (PI). The use of nasogastric suction, early parenteral nutrition, intravenous infusion of fluids, topical anesthesia, reduced use of intravenous narcotics, surgical procedures like laparoscopy which involves minimal intestinal manipulation, in of place a laparotomy, chewing gum, and other medicinal interventions (Jonson &Walsh 2009)( Holt &Kehlet 2000 )(Lubbers &Buurman&Luyer 2010)However, given the various results, the effectiveness of these methods have yet be demonstrated and confirmed (Jonson &Walsh 2009). Avicenna,who wasalso known as Ibn-e-Sina in the western world, lived during year’s 980-1037AD, a famous Iranian physician and philosopher. His journal of medicine “Al-Q?n?nf? al-?ibb [Canon of Medicine]” is Avicenna’s most renowned work. Avicenna’s’ Cannon of Medicine included very transparent and classified summaries of the entire medical knowledge of that time, rather than his clinical experiences and those of the past physicians(Tabei&Riazi 2009)(Turgut&Manduz&Tandogan 2010). Avicenna has been credited for his description and contributions on the etiology of various diseases, his theories and etiology of these diseases along with his documentation of the cures that have led to a series of successful medical treatments of these diseases. Avicenna and other physicians of Iranian traditional medicine had also considered an accumulation of gases (flatus) and secretions in the intestine as one of the reason for PI, but described differently (IbnSina 2005 p.262) Ileus has been purposed in books of traditional medicine under title of “Ilavoos”, while the physicians deemed it as a type of colitis but it differs from this term that colitisaffects the inner lining of the large intestine, which includes the colon and the rectum, while ileus is specific to small intestine and more hazardous than colitis(IbnSina 2005 p. 261). Avicenna has gathered a perfect classification for its symptoms in book “Al-Q?n?nf? al-?ibb [Canon of Medicine]”. However, it seems that what may be purposed as the main cause for ileus in patients post surgically is the accumulation of wind “Riah” in intestines(IbnSina 2005 p.263) wind is a product that is produced due to impact of innate heat (natural heat) of body on a dense substance inside the body. In other words,(your body’s process for breaking down food for energy) the weak innate heat affects on the given dense material, a stream-like heat may be produced, which will be converted into wind upon its’ concentration(Kermani 2008 p.606) According of the theory of the physician in the traditional Iranian medicine, trauma or injury of body (surgical incision) and hemorrhage are is a probable reason for the reduction of this instinctive heat that can be seen among these patients (Ibn Abbas 2009 p.388). In contrast, using narcotics and sedatives or anesthetics are classified as very cold and dense materials in traditional medicine and at the same time, the accumulated secretions in intestines may be purposed as adjunctive materials for producing wind (IbnSina 2005 p.262). An Empty stomach for long periods of time and spiritual stresses may also act as an agent for producing wind in these patients (Jorjani 2009 p.631). This produced wind may create disorders in performance of intestines in two ways. On the one hand, the wind can be accumulated in the body cavities and within limbs., much like the status in which flatus may be seen in the stomach and intestines; and creation of wind in the intestine may be accumulated inside muscular tissues, which will be followed by pain and intestinal atony and paralysis (IbnSina 2005 p.262). With deference to the above statements previously discussed, this hypothesis purposes that one of the causes for postoperative ileus is wind. Therefore, those drugs, which remove the produced dense wind in the digestive system, may contribute to the return of intestinal movement (peristalsis) in the post-surgical patient more quickly following the operation. Additionally, this theory could possibly be used and studied as a new method for prophylactic purpose and treatment of the patient’s postoperative ileus (PI) state.We would like to continue further discussions on the aspects of Persian traditional medicinal treatment of ileus in future articles.DOI: http://dx.doi.org/10.3126/ijls.v9i5.12709